2013
DOI: 10.1371/journal.pmed.1001545
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Syphilis Screening Using Point-of-Care Testing in Sub-Saharan African Countries: A Cost-Effectiveness Analysis

Abstract: Yukari Manabe and colleagues evaluate the cost-effectiveness and budget impact of antenatal syphilis screening for 43 countries in sub-Saharan Africa and estimate the impact of universal screening on averted stillbirths, neonatal deaths, congenital syphilis, and DALYs. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
117
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(122 citation statements)
references
References 39 publications
3
117
1
1
Order By: Relevance
“…In a study in sub-Saharan Africa only 40% of women were screened for syphilis [24]. Blood group testing was lower than 84% in the South African Study [19].…”
Section: Discussionmentioning
confidence: 92%
“…In a study in sub-Saharan Africa only 40% of women were screened for syphilis [24]. Blood group testing was lower than 84% in the South African Study [19].…”
Section: Discussionmentioning
confidence: 92%
“…Sua sensibilidade e especificidade foram comparáveis às de testes não treponêmi-cos utilizados na testagem de rotina realizada em clínicas de DST ou em serviços de pré-natal 28 . Sua utilização em locais com recursos limitados na África Subsaariana mostrou-se altamente custo-efetiva, mesmo se ocorrer redução da prevalência de sífilis na gestação 29 .…”
Section: Discussionunclassified
“…In fact, a recent bioethical assessment concluded that it would be ethically preferable to include stillbirths in burden of disease estimates, 19 such as the GHE, and several cost-effectiveness analyses focused on maternal health have included stillbirth in their DALY estimates. 5,20,21 In our model, stillbirths associated with maternal syphilis infection account for almost two-thirds of the disease burden (8.1 million DALYs). In fact, the burden associated with syphilis-related stillbirths is slightly below the public health burden associated with tuberculosis in the African region (9.4 million DALYs in 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, rapid, reliable and inexpensive immunochromatographic point-of-care tests were introduced that are reported to be highly cost-effective within antenatal care (ANC) settings. 5,6 A study in Tanzania reported no increased risk for adverse pregnancy outcomes among seropositive pregnant women that were treated with a single dose of intramuscular benzathine penicillin. 7 A meta-analysis of interventional studies concluded that adverse pregnancy outcomes can be prevented if infected mothers are identified and treated prior to the third trimester of pregnancy.…”
Section: Introductionmentioning
confidence: 99%